The Relationship between Drug Addiction with Age, Life Difficulties, and Level of Knowledge - Asadullah Kaliwal; Abdul Rahman Abid; Hamidullah Hamid (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
This study investigates the relationship between Drug addiction and factors such as adolescence, knowledge level, and life difficulties among teenagers in District 12 of Kabul city. The primary objective is to clarify how drug addiction among adolescents is associated with their age, awareness level, and life-related pressures. A sample of 140 adolescents from District 12 was selected for the study. Data were collected using a structured questionnaire consisting of 10 questions divided into two sections. The questionnaire’s reliability was confirmed with a Cronbach’s alpha of 0.82, and its validity was endorsed by 8 senior academic experts. The collected data were analyzed using SPSS version 21. The findings indicate that drug addiction among adolescents in this district does not have a strong correlation with age. However, there is a significant association between drug addiction and life stressors. Additionally, the level of knowledge showed a moderate relationship with drug addiction. The study concludes that other contributing factors should also be considered in understanding the causes of drug addiction among adolescents. The results may serve as a valuable resource for families and relevant institutions to develop strategies aimed at preventing drug usage among youth.